Numerical Simulation of Flood Routing using the Simplified Saint Venant Equations in Rectangular Channels - Bambang Agus Sulistyono; Samijo Samijo; Dian Devita Yohanie (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2021)
Floods, which cause a lot of damage, are a natural phenomenon that often occurs during the rainy season. Flood occurs because the discharge entering the channel exceeds the channel capacity. If the discharge data in the upstream area that will enter the channel is known, we can determine the flow behavior in the downstream area using a mathematical model. In this study, we proposed using simplified Saint Venant equations to simulate the flow routing in a prismatic channel with a rectangular section. This model is solved numerically using the finite difference method. Here, the numerical scheme used succeeds in simulating the flow behavior in the channel due to the discharge entering it. The simulation results show that the discharge entering the channel will propagate downstream with decreasing discharge quantity. Information on the amount of discharge at locations along the channel is useful as supporting data for flood control and prevention systems that will be conveyed to residents along the channel.Keywords: flood routing; prismatic channel; Saint Venant Equations; finite difference method. AbstrakBanjir yang menimbulkan banyak kerusakan merupakan fenomena alam yang sering terjadi pada musim hujan. Banjir terjadi karena debit yang masuk ke dalam kanal melebihi kapasitas kanalnya. Jika data debit di daerah hulu yang akan masuk ke dalam kanal diketahui, maka kita dapat menentukan perilaku aliran di daerah hilir dengan menggunakan model matematika. Dalam studi ini, kami mengusulkan untuk menggunakan persamaan Saint Venant yang disederhanakan untuk mensimulasikan penelusuran aliran pada saluran prismatik dengan penampang persegi panjang. Model ini diselesaikan secara numerik dengan menggunakan metode beda hingga. Di sini, skema numerik yang digunakan berhasil mensimulasikan perilaku aliran pada saluran akibat debit yang masuk. Hasil simulasi menunjukkan bahwa debit yang masuk ke saluran akan merambat ke hilir dengan kuantitas debit yang semakin berkurang. Informasi jumlah debit di lokasi sepanjang saluran ini berguna sebagai data pendukung pada sistem pengendalian dan pencegahan banjir yang akan disampaikan kepada penduduk di sepanjang kanal.Kata kunci: penelusuran banjir; saluran prismatik; persamaan Saint Venant; metode beda hingga.